Shiʿi Clerical Authority and Its Role in Iran’s Political Landscape (1941–2024) - Mikail, Kiki; Hadi, Abdul; Munir; Jody, Jeniwaty Moh. (Journal of Islamic Thought and Civilization, 2025)
This study explores the transformation of Shi’a clerical authority in Iran, examining how clerics have evolved from religious leaders to prominent political figures with enduring influence. By tracing the historical development of clerical authority from the occultation of the last Imam to the present, the research highlights the financial mechanisms that sustain the marjaʿ (leading cleric) in contrast to state-backed Sunni religious structures. Through qualitative analysis, such as historical context and case studies like the 2009 Iranian election and the Green Movement, the study reveals how clerics navigate political pressures, sometimes in tension with the regime. The findings indicate that while the Islamic Republic officially endorses clerical authority, the clerical elite—particularly in Qom—operates with considerable independence, bolstered by financial autonomy and skilled political communication. This research contributes to understanding the nuance between the Republic of Islam and the clerical establishment, suggesting that the economic and strategic positioning of Shi’a clerics ensures their lasting influence in Iranian religious and political spheres.